Meningkatkan Hasil Belajar Peserta Didik pada Materi Kegiatan Ekonomi melalui Media Pembelajaran Crossword Labs pada Kelas X.11 SMA N 3 Pekanbaru - Utami, Dwi Pangastuti; Helpita, Helpita; Sari, Dian Yusfita; Wulandary, Erika; Rahmasiwi, Ardika; Kamila, Cahya; Arisanti, Desi; Mujiono, Mujiono (UIR Press, 2025)
This study aims to analyze the improvement of students' learning outcomes in economic activity material through the use of Crossword Labs learning media in class X.11 SMAN 3 Pekanbaru. The background of the study is based on the low learning outcomes of students in economics learning which is considered difficult and less interesting. To overcome this, the researcher applied the Cooperative Learning model combined with Crossword Labs media to create an interactive and enjoyable learning atmosphere. This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model, which is carried out in two cycles through the stages of planning, action, observation, and reflection. The subjects of the study were 36 students of class X.11 who were selected through saturated sampling techniques. Data were analyzed quantitatively using a difference test (paired sample t-test) to determine the effectiveness of the learning media. The results showed a significant increase in learning outcomes, with most students experiencing an increase in grades. These findings indicate that Crossword Labs media is effective in improving students' learning outcomes in Economics subjects.